IL-23/Th17 Axis: A Potential Therapeutic Target of Psoriasis - Sharma, Amit; Upadhyay, Deepak K.; Gupta, Ghanshyam Das; Narang, Raj Kumar; Rai, Vineet Kumar (Current Drug Research Reviews, 2022)
Psoriasis is an immune-mediated skin disease that leads to the initiation of abnormal production of inflammatory mediators and keratinocytes hyper-proliferation. Th-1 cell expressing cytokines such as IL-1β and TNF-α have been the important hallmarks in the management of psoriasis. However, investigations carried out in the previous few years underline the involvement of another subset of T helper cells, i.e. Th-17 in psoriasis exacerbation, and hence have become the point of focus now. The immunopathogenesis of Th-17 is the result of the IL-23/Th-17 axis. It involves the release of IL-17 and IL-22 in response to the activated NF-kβ dependent activation of IL-23. The function of human Th-17 cells, as well as the crucial role of IL-23/Th-17 axis in the exacerbation of psoriasis and treatment, have been well explored. Therefore, considering IL-23/Th17 axis as a pertinent therapeutic target in immune driven disorders, extensive investigations are now highlighting the utility of biopharmaceuticals and/or biological agents acting on these targets. Here, we review the IL-23/Th-17 axis based therapeutic targets, different types of active moieties based on their source of availability and most useful USFDA approved Mabs targeting the IL-23/Th17 axis in psoriasis for a better understanding of the future possibilities in this area.
Keywords: therapeutic targets